2014
DOI: 10.3346/jkms.2014.29.3.338
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram for Prediction of Prostate Cancer with Serum Prostate Specific Antigen Less than 10 ng/mL

Abstract: Although prostate-specific antigen (PSA) is a very useful screening tool, prostate biopsy is still necessary to confirm prostate cancer (PCA). However, it is reported that PSA is associated with a high false-positive rate and prostate biopsy also has various procedure-related complications. Therefore, the authors have devised a nomogram, which can be used to estimate the risk of PCA, using available clinical data for men with a serum PSA less than 10 ng/mL. Prostate biopsies were obtained from 2,139 patients f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
1
11
0
1
Order By: Relevance
“…Seo, et al 32 reported that the prostate cancer detection rate of Korean men with PSA levels under 10 ng/mL was 19.6%. Similarly, according to Ahn, et al, 33 the detection rate of our institute during the last 13 years was 21.8%. Even with variation in the study cohorts, or the presence of selection or sampling bias, the gap in detection rate between the present study and current literatures is substantial.…”
Section: Discussionsupporting
confidence: 72%
“…Seo, et al 32 reported that the prostate cancer detection rate of Korean men with PSA levels under 10 ng/mL was 19.6%. Similarly, according to Ahn, et al, 33 the detection rate of our institute during the last 13 years was 21.8%. Even with variation in the study cohorts, or the presence of selection or sampling bias, the gap in detection rate between the present study and current literatures is substantial.…”
Section: Discussionsupporting
confidence: 72%
“…A nomogram is a graphical tool and can be used for anyone to a predict prevalence rate because it is calculated by adding points. It has been developed for many diseases studied in preventive medicine or diagnostic medicine (Ahn et al, 2014;Kattan et al, 1998;Kim et al, 2016). In this study, we introduced nomogram based on naïve Bayesian classifier model and applied it to CVD data from KN-HANES 2013-2015.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…However, to the best of our knowledge, this study included the largest number of patients with PSA levels in the “gray zone” in a Chinese population. Second, other models that predict the risk of prostate cancer among men with PSA levels between 4 and 10 ng/ml exist [20] , [21] . Nevertheless, compared with other models, our model had a higher AUC (0.789 vs. 0.73 and 0.759 respectively) and higher predictive accuracy based on PSA alone (0.223 vs. 0.11 and 0.182 respectively), which indicated that our model is more reliable and could identify more patients with a high risk for prostate cancer as shown in Table 4 .…”
Section: Discussionmentioning
confidence: 99%